Slothilda : living the sloth life - Fabiero, Dante, 1983- (Skyhorse Publishing, 2018)
"... a charming collection of comics about an ambitious little sloth who'd rather just take it easy. With themes related to work, fitness, food, shopping, home life, and pets--this book shows that you're not the only sloth at heart."--Back cover.